Analisis Perilaku Phubbing (Phone Snubbing) dan Penanganannya - Rismiyana, Rismiyana; Umar, Nur Fadhilah; Buchori, Sahril (ILIN Institute, 2024)
This research analyzes the phubbing behavior of JN at SMAN 3 Makassar. The purpose is to know 1) The description of phubbing behavior on JN at SMAN 3 Makassar, 2) The cause of JN's phubbing, 3) Handling phubbing on the subject of JN. This research uses a qualitative approach. the type of research is a clinical case study. Data collection through interviews, observations and documentation studies and using qualitative analysis of the Miles & Huberman model, namely data reduction, data presentation and conclusion drawing. The results 1) The description of JN's phubbing behavior is playing smartphones when the teacher teaches, less socializing, looking at smartphones when interacting 2) The causative factors are internal factors: lack of self-control, habits, boredom proneness. External factors: Following and being ignored by friends. 3) The handling, researchers apply behavior contract techniques to reduce behavior. After handling, subject JN can reduce his phubbing.